2018
DOI: 10.1002/ejoc.201800880
|View full text |Cite
|
Sign up to set email alerts
|

Anion Recognition by Partial Cone Dihomooxacalix[4]arene‐Based Receptors Bearing Urea Groups: Remarkable Affinity for Benzoate Ion

Abstract: Tetraureido‐dihomooxacalix[4]arenes (tert‐butyl 4a and phenyl 4b) were synthesised and obtained in a partial cone conformation in solution and in the solid state, as confirmed by NMR and X‐ray diffraction studies. Their complexation ability towards halides, pseudo‐halides and oxoanions was assessed by 1H NMR and UV/Vis titrations. Structural and energetic insights of phenylurea 4b complexes were also obtained using molecular dynamics (MD) simulations. The binding data showed that the association constants are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The facing butoxy substituted phenyl ring (D) is inclined slightly outwards, with a dihedral angle of 101°. Consistently with previous reports, the ureido groups form an intramolecular N–H···O bifurcated hydrogen bond (Marcos et al, 2014b; Augusto et al, 2018). In this case the H-bond is rather asymmetric, with the N···O distance of the NH directly bonded to the phenyl ring, para to the electron-withdrawing CF 3 group, shorter with respect to the other N···O distance (2.89 vs. 3.06 Å).…”
Section: Resultssupporting
confidence: 92%
“…The facing butoxy substituted phenyl ring (D) is inclined slightly outwards, with a dihedral angle of 101°. Consistently with previous reports, the ureido groups form an intramolecular N–H···O bifurcated hydrogen bond (Marcos et al, 2014b; Augusto et al, 2018). In this case the H-bond is rather asymmetric, with the N···O distance of the NH directly bonded to the phenyl ring, para to the electron-withdrawing CF 3 group, shorter with respect to the other N···O distance (2.89 vs. 3.06 Å).…”
Section: Resultssupporting
confidence: 92%
“…The association constants, as log K ass and reported in Table , were determined following the urea NH chemical shifts through the WinEQNMR2 program . In the case of the partial cone receptors, the data were calculated using the NH chemical shifts of the two (thio)ureido groups oriented on the same side of the macrocyclic ring …”
Section: Resultsmentioning
confidence: 99%
“…As part of our interest in the study of homooxacalixarenes (calixarene analogues in which the CH 2 bridges are partly or completely replaced by CH 2 OCH 2 groups) we have reported the anion binding affinity of several di‐, and tetra‐substituted (thio)ureido‐dihomooxacalix[4]arenes, in the cone conformation incorporating a four carbon atom spacer. Tetra‐substituted dihomooxa receptors in a partial cone conformation and bearing a propyl spacer were also studied . In general, we observed that phenylurea receptors are more efficient than phenylthioureas, the substituents (alkyl/aryl) on the urea moiety deeply affect the complexation ability, the phenylurea derivatives are the strongest receptors, and a higher number of potential hydrogen‐bond donors enhances the binding affinity.…”
Section: Introductionmentioning
confidence: 98%
“…As part of our on-going interest on the host-guest properties of substituted dihomooxacalix[4]arenes (calix[4]arene analogues in which one CH 2 bridge is replaced by one CH 2 OCH 2 group) with (thio)urea units [ 19 , 20 , 21 , 22 , 23 ], we have extended our research into the study of fluorescent receptors for anion [ 24 ] and ion-pair recognition. Thus, dihomooxacalix[4]arene-based fluorescent sensors bearing (thio)urea groups as a binding site and naphthalene moieties as a fluorophore unit were obtained for the first time.…”
Section: Introductionmentioning
confidence: 99%